The Influence of Play Therapy Arranging A Tower of Donut on Improving The Motor Ability of Down Syndrome Children at The Foundation For The Development of Disabled Children (Ypac) Makassar - Sanghati, Sanghati (ScieClouds Publishing, 2023)
The aim of this research is to determine the effect of play therapy arranging donut towers on improving the motor skills of children with Down syndrome at the Makassar Foundation for the Development of Disabled Children (YPAC) . The method used in this research is